The Utilization of Sugarcane Waste As an Alternative Material of Halal Hard Capsules Shell - Alwi, Zulfahmi; Arsul, Muhammad Ikhlas (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2025)
Capsules are dosage forms used to encapsulate powders, granules, pellets, liquids, and semi-solids. There are two types of capsules: soft capsules, which are usually used to encapsulate liquid and semi-solid formulas, and hard capsules, which are used to encapsulate solid formulas and non-aqueous liquids. This research aims to analyze the halal critical point of cellulose production and hard capsule shell from sugarcane waste and its handling solution, make sugarcane waste into quality halal cellulose according to pharmaceutical standards, and formulate halal cellulose into quality hard capsule shell according to pharmaceutical standards. Analyzed halal were done by material and procedure. Extraction cellulose by acetylation. Characterization of cellulose followed yield, viscosity, and swelling. Capsule shelll characterization followed size and disintegration time. This study concludes that the source of ethanol in capsule shell production is key to determining its halal status. The process must avoid using haram materials like pork, its derivatives, human body parts, khamr, blood, carrion, improperly slaughtered animals, and forbidden animals. Instead, sugarcane waste can be used to produce halal cellulose, which meets pharmaceutical standards and can be used to make hard capsule shells that are both halal and meet industry requirements.